Theoretical and Computational Basis for Economical Ressource Allocation in Application Layer Networks - Annual Report Year 1 - Torsten Eymann; Michael Reinicke; Werner Streitberger; Björn Schnizler; Daniel Veit; Felix Freitag; Isaac Chao; Pablo Chacin; Dirk Neumann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2005)
This paper identifies and defines suitable market mechanisms for Application Layer Networks (ALNs). On basis of the structured Market Engineering process, the work comprises the identification of requirements which adequate market mechanisms for ALNs have to fulfill. Subsequently, two mechanisms for each, the centralized and the decentralized case are described in this document.
urn:nbn:de:bvb:703-opus-3577
Keywords: 004; Grid Computing